Development of Muallimin Curriculum Model Based on Muadallah System A Case Study of Pondok Modern Darussalam Gontor, Indonesia - Siska Pratiwi (Prince of Songkla University, 2023)
Thesis (M.Ed., Islamic Educational Administration and Management)--Prince of Songkla University, 2020